Factors associated with the development of epilepsy in very low birth weight infants - Toshimichi Fukao; Fumikazu Sano; Atsushi Nemoto; Atsushi Naito; Toshimitsu Yanagisawa; Ken Imai; Takehiko Hiroma; Yuji Inaba; Hideaki Kanemura; Masao Aihara; Takeshi Inukai; Yoshimi Kaga (Elsevier, 2023)
Background: The survival rate of very low birth weight (VLBW) infants has recently improved. However, the occurrence of and factors associated with epilepsy in VLBW infants remain unknown. This study aimed to clarify the incidence, characteristics, and factors associated with epilepsy development in VLBW infants. Methods: All VLBW infants admitted to our hospital between 2012 and 2017 were included in this study. VLBW infants with a follow-up period of <1 year were excluded. Chromosomal abnormalities, brain anomalies, severe intraventricular hemorrhage (IVH), cystic periventricular leukomalacia (PVL), and hypoxic ischemic encephalopathy (HIE) were considered to be risk factors. Results: Epilepsy occurred in 21/526 (4.0%) VLBW infants. Chromosomal abnormalities, brain anomalies, severe IVH, cystic PVL, HIE, neonatal seizures, advanced maternal age, maternal diabetes mellitus, no administration of antenatal corticosteroids, and low Apgar scores at 1 and 5 min were associated with a risk of epilepsy. The median time to epilepsy onset was 8 months (range: 0-59 months), and the onset occurred within 2 years in 15/21 patients (71.4%) and within 4 years in 18/21 patients (85.7%). VLBW infants with risk factors developed epilepsy earlier and at a significantly higher rate than those without risk factors. Among infants who had risk factors and who developed epilepsy, 86.7% did so within 2 years of age, compared to 33.3% of those who developed epilepsy but did not have risk factors. Conclusion: These findings regarding factors associated with a risk of development of epilepsy and temporal feature of epilepsy may contribute to the development of monitoring and treatment protocols for epilepsy in VLBW infants.